Strategic Planning Information Systems Industrial Work Lecture Program (Case Study: CV. Laksana Karoseri) - Kevin Duta Auliawan; Hanna Prillysca Chernovita (Journal of Information System and Informatics, 2022)
CV. Laksana Karoseri is a bus carousel company from Ungaran that assembles various bus bodies. In an effort to help the development of good human resources, every year CV. Laksana Karoseri has an industrial work lecture program that accepts hundreds of internship students every year. However, the program has not been running and is well organized because some activity processes have not run optimally, for example, the acceptance of internships, attendance and scheduling of internships that are not managed properly. Therefore, it is necessary to have SI / IT strategic planning to improve management and deal with problems that occur in industrial work lecture programs at CV. Laksana Karoseri. This research was conducted by conducting interviews and observations on CV. Laksana Karoseri. The method used to carry out this SI / IT strategic planning is the Ward and Peppard method which includes Value Chain, SWOT, PEST and Five Force Model analysis which then produces an application portfolio, namely the Registration Information System and Industrial Work Lecture Details, the website and mobile version of the Scheduling and Attendance Information System, the Weekly Activity Log Book Information System and the Internship Report Document Archive Information System which was mapped using McFarlan's analysis. The results of the SI/IT strategic plan will be implemented within four years.